Intervención del terapista respiratorio en paciente femenino de 66 años con diagnóstico de enfisema pulmonar. - Barcos Quinto, Anggie Lucero (2022)
Pulmonary emphysema is a chronic, progressive, disabling and fatal disease caused by a phenomenon of static and dynamic hyperinflation that causes a reduction in expiratory flows. Medical treatment offers limited benefits, which is why lung volume reduction techniques have been developed that attempt to eliminate damaged or hyperinflated areas of the lung to improve respiratory mechanics and symptoms. (EXHIBIT, 2016). The first technique was lung volume reduction surgery, but this conditioned a high price for patients in the sense of an increase in complications and mortality; That is why endoscope lung volume reduction techniques have emerged, which are less invasive and have less morbidity and mortality. (EXHIBIT, 2016). In our study we want to determine the clinical, radiological and functional factors that predict future complications and mortality. On the other hand, we value the reduction in residual volume as an expression of the improvement in air attraction. (EXHIBIT, 2016).